A new species of the genus Alienates Barber (Hemiptera: Heteroptera: Enicocephalidae: Alienatinae) from Venezuela - Baňař, Petr; Štys, Pavel; Kolesnichenko, Yuliya (Zootaxa, 2015)
New species Alienates thomasi sp. nov. Baňař & Štys is described from Venezuela based on a single female. It is the first species recorded from South America, and is illustrated and compared with other Caribbean and Central American Alienates species